Experimental Verification of the Effectiveness of the Pedagogical System of the Formation of Educational Environment in a Higher Educational Institution - Marchenko, O. H.; Марченко, О. Г.; Onypchenko, P.; Zelenska, O.; Zhovtonizhko, I.; Barannyk, M.; Ольга Марченко (The New Educational Review. - 2023. - Vol. 71. - P. 50-62, 2023)
Дослідження пов'язане з педагогічним експериментом системного керованого впливу на формування освітнього середовища у вищому навчальному закладі. Метою статті є перевірка ефективності запровадження педагогічної системи формування освітнього середовища у вищому навчальному закладі на прикладі авіаційного навчального закладу.

The study is related to the pedagogical experiment on the systemic controlled impact on the formation of educational environment in higher educational institutions. The article aims to verify the effectiveness of introducing the pedagogical system of educational environment formation in higher educational institutions on the example of an aviation educational institution. Evaluation of the effectiveness of the pedagogical system of educational environment formation is based on the monitoring analysis. Diagnostic techniques of the expert examination have been described. The statistical insignificance of discrepancies between the data of control and experimental samples has been proved. Significant changes in the educational environment formation levels in the control and experimental groups have been confirmed.

Исследование связано с педагогическим экспериментом по системному контролируемому влиянию на формирование образовательной среды в высшем учебном заведении. Целью статьи является проверка эффективности внедрения педагогической системы формирования образовательной среды в высшем учебном учреждения на примере авиационного учебного заведения.
Keywords: освітнє середовище; педагогічна система; вищий військовий навчальний заклад; авіаційне спрямування; educational environment; pedagogical system; higher military educational institution; aviation-oriented; образовательная среда; педагогическая система; высшее военное учебное заведение; авиационная направленность